2004
DOI: 10.1007/s00125-004-1586-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of glucose and insulin on vascular endothelium

Abstract: Aims/hypothesis. Chronic exposure to high concentrations of glucose has consistently been demonstrated to impair endothelium-dependent, nitric oxide (NO)-mediated vasodilation. In contrast, several clinical investigations have reported that acute exposure to high glucose, alone or in combination with insulin, triggers vasodilation. The aim of this study was to examine whether elevated glucose itself stimulates endothelial NO formation or enhances insulin-mediated endothelial NO release. Methods. We measured NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
1
23
0
2
Order By: Relevance
“…The same group, however, failed to show changes in BAECs after a 24-h exposure to high glucose (Kaiser et al 1993). Taubert et al (2004) demonstrated that, in a study with passage 2 porcine aortic endothelial cells, 20 mmol/L Dglucose, but not L-glucose, induced an increase in intracellular calcium and a transient release of NO that was inhibited by either the sodium/calcium exchange (NCX) inhibitor, dichlorobenzamil, or the SGLT-1 inhibitor, phlorizin. D-glucose also augmented the vasodilator action of insulin and enhanced insulin-induced relaxation of porcine artery ring preparations as well as insulin-mediated NO response in porcine aortic endothelial cells; interestingly prolonged exposure to 25 mmol/L D-glucose resulted in a progressive loss of NO release and after 2 h complete inhibition (Taubert et al 2004).…”
Section: Glucose Transport Into Endothelial Cellsmentioning
confidence: 91%
See 3 more Smart Citations
“…The same group, however, failed to show changes in BAECs after a 24-h exposure to high glucose (Kaiser et al 1993). Taubert et al (2004) demonstrated that, in a study with passage 2 porcine aortic endothelial cells, 20 mmol/L Dglucose, but not L-glucose, induced an increase in intracellular calcium and a transient release of NO that was inhibited by either the sodium/calcium exchange (NCX) inhibitor, dichlorobenzamil, or the SGLT-1 inhibitor, phlorizin. D-glucose also augmented the vasodilator action of insulin and enhanced insulin-induced relaxation of porcine artery ring preparations as well as insulin-mediated NO response in porcine aortic endothelial cells; interestingly prolonged exposure to 25 mmol/L D-glucose resulted in a progressive loss of NO release and after 2 h complete inhibition (Taubert et al 2004).…”
Section: Glucose Transport Into Endothelial Cellsmentioning
confidence: 91%
“…Increased production of hydrogen peroxide in endothelial cells will also increase PKC activity (Taher et al 1993) and this will lead to a decrease in eNOS activity via PKC-mediated phosphorylation of eNOS specifically at Thr497 (Matsubara et al 2003). However, as already noted, in vivo the contribution of both endothelial and platelet eNOS activation by glucose must be considered (Massucco et al 2005;Taubert et al 2004).…”
Section: Effects Of High Glucose On Endothelial Function In Vitro Vsmentioning
confidence: 91%
See 2 more Smart Citations
“…For both hyperglycemic groups, we selected target glycemia of 250 -350 mg/dl, because this level is in the range commonly chosen by other authors in experimental (17)(18)(19)(20)(21) and clinical studies (6,22). Thus, these levels allow us to compare our results with those from previous clinical and experimental studies.…”
Section: Methodsmentioning
confidence: 99%